2010
DOI: 10.1021/ja9097725
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ion-Paired Iridium Complexes (Soft Salts) and Their Application in Organic Light Emitting Diodes

Abstract: Three Ir-based materials were synthesized through metathesis reaction between halide and alkali metal salts of two cationic and three anionic Ir complexes, respectively. The resulting "soft salt" complexes are composed of an organometallic cation and an organometallic anion. The electrochemical and photophysical characterization of these compounds is reported. The redox potentials of the soft salts are shown to be determined by the lowest energy potentials of the two ions. Energy transfer between the ions in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 39 publications
6
98
0
Order By: Relevance
“…Complex 2: (Reported) (Leung et al, 2013b). Complex 3: (Reported) (Wu et al, 2010). Complex 4: (Reported) .…”
Section: Synthesismentioning
confidence: 99%
“…Complex 2: (Reported) (Leung et al, 2013b). Complex 3: (Reported) (Wu et al, 2010). Complex 4: (Reported) .…”
Section: Synthesismentioning
confidence: 99%
“…Among all triplet emitters under investigations, iridium complexes have been identified as the most promising candidates as these organometallic complexes have high photoluminescence quantum yields at room temperature, relatively short excited state lifetimes and excellent color tunability [9]. So far, neutral [10][11][12][13][14], cationic [15][16][17][18], anionic [19][20] and even soft salts [21][22][23] where both the anionic and the cationic complex can contribute to light emission were successfully used as triplet emitters for electroluminescent devices.…”
Section: Introductionmentioning
confidence: 99%
“…24 The room temperature quantum yields (QY) of the Ir1 and Ir2 complexes were 52 and 45%, respectively. Wu C. et al 25 reported the photophysical properties of cationic Ir(III) complexes with soft anions and found QY values were sensitive to ligand size and counter ion nature, and found that greater steric hindrances increased QYs by increasing distance between iridium complexes. Moreover, soft salts, such as PF 6 −1 salts, have higher QYs than halide salts because larger anion sizes increase intermolecular distances.…”
Section: Resultsmentioning
confidence: 99%